Using ‘Medicalenglish’ to Improve EFL Students’ Reading Motivation: a Case Study in Nursing Department - Anny Sulistyo Rini; Aji Budi Rinekso (PAEDAGOGIA, 2021)
The importance of reading comprehension is immense. It contributes to the success of language learning and teaching. However, there are some factors such as less interesting and difficult text sources and other non-contextual factors that demotivate the students in reading. To deal with that issue, the implementation of a Learning Management System (LMS) called MedicalEnglish is introduced to the students in order to amplify the students’ motivation in learning English. This study is intended to investigate the motivation of 22 Diploma students of the Nursing department in Semarang in reading using MedicalEnglish. In this qualitative case study, questionnaire and interview were selected as the instrument. The data collected from the two instruments were then descriptively elaborated. In conclusion, there is a significant improvement in students’ motivation in learning reading after the implementation of MedicalEnglish. The result of this study is expected to provide additional reliable sources regarding the implementation of LMS in sustaining students’ reading motivation.